A reunião de processos na execução trabalhista - Teixeira, Marcio Fernandes (2024)
This work aims to discuss the effectiveness of execution in the Labor Court, through the gathering of processes in the execution phase, as well as the respective developments. The research approaches the historical context, in order to situate the problem involving conflicts of interest between employees and employers. It is necessary to conceptualize the company as a source of salary, without forgetting its objective of earning profits, nor its social function. The employer's powers over the employee are enumerated, as the exercise of these powers may give rise to labor complaints that will give rise to the execution of sentences, the object of this study. With the same concern regarding the origin of the demands, the principles that govern Labor Law and Labor Procedural Law are analyzed, especially in their main characteristic, which is the protection of the employee. The study addresses alternative ways to resolve labor disputes, as well as the litigious culture of actors in the labor relationship in Brasil, which ends up clogging up the courts, with thousands of labor complaints filed annually. This congestion has its biggest bottleneck in the execution phase of the judgments, requiring solutions from the Judiciary and society as a whole. The Labor Court has been trying to make the execution phase of its sentences more effective, promoting the gathering of processes in the execution phase. The solution found by the Labor Court is supported by the publication of provisions, within the scope of the General Inspectorate of the Labor Court and in the regional inspectorates, which attempt, without success, to unify the procedures relating to the collection of executions in the labor courts. This study points out the problems involving the collection of executions within the scope of the Labor Court, bringing solutions, through the need to issue an ordinary law, which will unify and make the procedures cogent, to better manage this new dynamic, which is of vital importance to maintain the functioning of companies, the maintenance of jobs and the payment of credits recognized in court.